Evaluation of submarine atmospheres: effects of carbon monoxide, carbon dioxide and oxygen on general toxicology, neurobehavioral performance, reproduction and development in rats. I. Subacute exposures. (February 2015) - Hardt, Daniel J.; James, R. Arden; Gut, Chester P.; McInturf, Shawn M.; Sweeney, Lisa M.; Erickson, Richard P.; Gargas, Michael L.
Abstract The inhalation toxicity of submarine contaminants is of concern to ensure the health of men and women aboard submarines during operational deployments. Due to a lack of adequate prior studies, potential general, neurobehavioral, reproductive and developmental toxicity was evaluated in male and female rats exposed to mixtures of three critical submarine atmospheric components: carbon monoxide (CO) and carbon dioxide (CO2; levels elevated above ambient), and oxygen (O2; levels decreased below ambient). In a 14-day, 23 h/day, whole-body inhalation study of exposure to clean air (0.4 ppm CO, 0.1% CO2 and 20.6% O2), low-dose, mid-dose and high-dose gas mixtures (high dose of 88.4 ppm CO, 2.5% CO2 and 15.0% O2), no adverse effects on survival, body weight or histopathology were observed. Reproductive, developmental and neurobehavioral performance were evaluated after a 28-day exposure in similar atmospheres. No adverse effects on estrus phase, mating, gestation or parturition were observed. No developmental or functional deficits were observed in either exposed parents or offspring related to motor activity, exploratory behavior or higher-level cognitive functions (learning and memory). Only minimal effects were discovered in parent-offspring emotionality tests. While statistically significant increases in hematological parameters were observed in the offspring of exposed parents compared to controls, these parameters remained within normal clinical ranges for blood cells and components and were not considered adverse. In summary, subacute exposures to elevated concentrations of the submarine atmosphere gases did not affect the ability of rats to reproduce and did not appear to have any significant adverse health effects.